SUBSTANTIATION OF OPERATION SERVICE MODES OF HOUSEHOLD WOOD WASTE CHOPPER - Lyashenko, S. V.; Sivtsov, O. V.; Zaporozhets, Y. V.; Koshkalda, S. I.; Shevchenko, V. V. (Scientific Progress & Innovations, 2020)
Leading countries of the world are replacing traditional energy resources with their alternatives, including those of plant origin. Ukraine is no exception, so using wood and its waste in thermal energy production is a topical issue today, especially for owners of private farms. As the raw material potential of firewood has been rapidly declining in recent years, the search for alternatives leads to using wood waste, namely branches. Wood and branch waste is a raw material that can be processed into fuel chips, which are a crisis-resistant fuel, especially for private farms. The efficiency of biomass processing into energy products is achieved only with rational operating parameters of machines and technological processes. Thus, the study of operating modes of household wood chipper is an important scientific and applied task today. The purpose of the work is to substantiate the operation service modes of household chopper of wood waste for the production of fuel on personal farms. The main objectives of this work were choosing optimal operating modes and design parameters for a small chopper of wood waste and improving the mathematical model of the influence of material density and cutting angle on energy consumption of the technological process of its grinding. Production tests of the chopper were conducted and technical and economic indicators of its operation were established. To improve the mathematical model, the methods of physical and mathematical modeling of a real chopper and methods of mathematical statistics were used in processing and analyzing experimental data. As a result of the work, it has been found that the range of chopper rational values, namely wood slope at feeding cutting wood waste is in the range of 30000´… 36038´ and the density of grinding material – in the range of 440 kg/m3… 530 kg/m3. In this case, power consumption of the household chopper electric motor will be W = 1.30… 1.40 kW/h, which is the optimal value. Based on production research, it has been established that the obtained equation makes it possible to determine the limits of energy consumption depending on the density of the material and feeding slope during the technological process of grinding wood waste.